2007
DOI: 10.1002/app.27024
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of silver nanocrystals by a modified polyol method

Abstract: A modification of the polyol method has been shown to result in improved efficiency and enhanced kinetics for the synthesis of silver nanocrystals when compared with the traditional polyol method. The Ag nanocrystals produced were characterized using Xray diffraction and transmission electron microscopy. Accordingly, the exhibited Ag crystal structure, corresponding lattice constants, and resultant particle sizes were determined by these means. In addition, using Fourier transform infrared spectroscopy, it was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 20 publications
1
14
0
Order By: Relevance
“…The absorption peak at 1289 cm −1 corresponds to the C-N bond vibration. In addition, the absorption peak at 649 cm −1 indicates the existence of the swing to the face of the C-H bond vibration peak [15,20].…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…The absorption peak at 1289 cm −1 corresponds to the C-N bond vibration. In addition, the absorption peak at 649 cm −1 indicates the existence of the swing to the face of the C-H bond vibration peak [15,20].…”
Section: Resultsmentioning
confidence: 98%
“…The plasmon resonance absorption of AgNP occurs in a specific wavelength [15]. The emergence of characteristic absorption peaks in the spectra can represent the performance of a specific color rendering solution.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…17 It is proposed that polar groups, such as the CO groups of PVP chain, can interact with metal ions and form coordinating complex. 18 It is suggested that electron clouds are strongly partial to oxygen in polar carbonyl group (CO) and nitrogen atom transfers its electrons to pyrrolidone ring of PVP. Correspondingly, chemical reaction can take place between PVP and metal ions, in which metal ions receive lone pair electrons from the ligands −N and CO group in pyrrolidone ring and form atomic metal that further grows into particles.…”
Section: Introductionmentioning
confidence: 99%
“…It is broadly used in areas such as medicine, food, cosmetics, and health-related domains [39]. In a recent work [40][41][42][43][44][45], it was found that poly(vinylpyrrolidone) plays an important role in determining the final shape of nanocrystals. Thanks to the efforts of several research groups, the polymerdirect process has become an effective method in controlling the growth of metals nanostructure.…”
Section: Introductionmentioning
confidence: 99%